2004
DOI: 10.1113/expphysiol.2004.028159
|View full text |Cite
|
Sign up to set email alerts
|

Promoters and serotypes: targeting of adeno‐associated virus vectors for gene transfer in the rat central nervous system in vitro and in vivo

Abstract: The brain parenchyma consists of several different cell types, such as neurones, astrocytes, microglia, oligodendroglia and epithelial cells, which are morphologically and functionally intermingled in highly complex three-dimensional structures. These different cell types are also present in cultures of brain cells prepared to serve as model systems of CNS physiology. Gene transfer, either in a therapeutic attempt or in basic research, is a fascinating and promising tool to manipulate both the complex physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
147
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(155 citation statements)
references
References 26 publications
6
147
0
2
Order By: Relevance
“…32,33 Of course, increased transduction and stronger transgene expression from gene therapy applications may not necessarily lead to better outcomes, and there is likely to be a fine balance between therapeutic and detrimental expression levels, especially for genes that encode secretable proteins. [34][35][36] This should also be taken into account when choosing promoters that may increase the specificity of transgene expression [37][38][39] and when designing vector systems that allow the temporal regulation of transgene expression. [40][41][42][43] Although comparable in terms of overall transduction efficiency, the tropism profile between rAAV2/2 and rAAV2/6 was considerably different.…”
Section: Discussionmentioning
confidence: 99%
“…32,33 Of course, increased transduction and stronger transgene expression from gene therapy applications may not necessarily lead to better outcomes, and there is likely to be a fine balance between therapeutic and detrimental expression levels, especially for genes that encode secretable proteins. [34][35][36] This should also be taken into account when choosing promoters that may increase the specificity of transgene expression [37][38][39] and when designing vector systems that allow the temporal regulation of transgene expression. [40][41][42][43] Although comparable in terms of overall transduction efficiency, the tropism profile between rAAV2/2 and rAAV2/6 was considerably different.…”
Section: Discussionmentioning
confidence: 99%
“…Kugler and colleagues have shown that gene expression from AAV2 or AAV5 can be restricted to neurons in vitro by incorporating the hSYN or CBA promoter or restricted mainly to astrocytes by using the mCMV promoter [18,20,27]. The hSYN promoter also confers neuronal specificity in vivo [20,27].…”
Section: Discussionmentioning
confidence: 99%
“…Kugler and colleagues have shown that gene expression from AAV2 or AAV5 can be restricted to neurons in vitro by incorporating the hSYN or CBA promoter or restricted mainly to astrocytes by using the mCMV promoter [18,20,27]. The hSYN promoter also confers neuronal specificity in vivo [20,27]. Klein, Meyer and colleagues have demonstrated transduction of cultures of astrocytes, microglia and cortical neurons using AAV2 or AAV8 with the CBA promoter [12,17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Second, long-term expression, from months to years, is achievable. Due to high rate of infectivity, rAAV can be used to introduce multiple genes into the same neurons in pre-selected brain regions (Shevtsova et al, 2005) without epigenetic silencing (Zhu et al, 2007). This broadens the experimental possibilities so that other genes whose products act as biosensors for different signaling systems, such as for calcium (Miyawaki, 2003;Palmer and Tsien, 2006;Wallace et al, 2008) and neurotransmitter release (Miesenbock et al, 1998), could also be introduced into the same neuron using rAAV as the delivery method.…”
Section: Introductionmentioning
confidence: 99%